Quality of Research for Development: Insights and Way Forward - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
The ISPC is facilitating System-wide agreement on the nature and assessment of Quality of Research for Development (QoR4D). A small working group (WG) on QoR4D with representation from Centers, CRPs and the IEA was established late last year. This WG organized a workshop at FAO on 06-07 February 2017 with representation from across CGIAR System constituencies - key findings from those discussions are elaborated in this brief.